A 93 year old man with the PRSS1 R122H mutation, low SPINK1 expression, and no pancreatitis: insights into phenotypic non-penetrance. Issue 5 (14th December 2005) - Khalid, A; Finkelstein, S; Thompson, B; Kelly, L; Hanck, C; Godfrey, T E; Whitcomb, D C
Abstract : Background: The cationic trypsinogen ( PRSS1 ) R122H mutation causes autosomal dominant hereditary pancreatitis (HP) with multiple attacks of acute pancreatitis, but the penetrance, frequency, and severity of attacks are highly variable. HP twins study suggests that modifier genes influence severity but not penetrance. Aim: To investigate potential trypsin associated factors in subjects with the PRSS1 R122H mutation and phenotypic non-penetrance. Methods: Two subjects from HP families (including a 93 year old subject with PRSS1 R122H without pancreatitis), one with chronic pancreatitis and one with a normal pancreas, were studied. Relative expression of: (a) the PRSS1 R122 and H122 alleles; and (b) the PRSS1 and SPINK1 genes in pancreatitis were determined using complementary methods. Results: PRSS1 wild-type (R122) and mutant (H122) allele expression was equivalent in multiple (>3) samples from the phenotypically affected and non-penetrant subjects with R122H genotypes using allele specific quantitative reverse transcription-polymerase chain reaction (RT-PCR) and intron spanning nested RT-PCR followed by cDNA sequencing. Compared with PRSS1 mRNA levels, SPINK1 mRNA levels were low in normal appearing tissue but markedly increased in samples with chronic inflammation, independent of PRSS1 genotype. Conclusion: Attacks of acute pancreatitis in HP subjects appear to be independent of the relative expression of the mutant PRSS1 H122 allele or SPINK1 gene expression. The marked increase in SPINK1 gene expression with inflammation is consistent with its regulation as an acute phase protein.